Eksperimen Pembelajaran Dengan Strategi Problem BasedLearning Dan Group Investigation Terhadap Hasil BelajarMatematika Ditinjau Dari Motivasi Siswa Kelas VIIISMP Negeri 1 Surakarta Semester GenapTahun Ajaran 2015/2016 - Rachmawati Wahyu Saputri, Ika; Prof.Dr. Sutama, M.Pd (2016)
ABSTRACT Ika Rachmawati Wahyu Saputri / A410120061. Learning experiment using Problem Based Learning and Group Investigation Strategy Toward Mathematics Learning Outcomes Observed of Students Motivation Grade VIII Academic Year 2015/2016. Research Paper. Faculty Of Teaching And Education Training, Muhammadiyah University Of Surakarta. June, 2016. This research three purposes. (1) Analize and examine the different effect of the implementation Problem Based Learning and Group Investigation toward mathematics learning outcomes, (2) analize and examine the different effect of student motivation toward mathematics learning outcomes, and (3) analize and examine interaction between learning strategies with student motivation towards mathematics learning outcomes. The type of this research is quantitative with quasiexperimental design. The population in this research is all students of VIII SMP Negeri 1 Surakarta of academic year 2015/2016. Sample of this research consisted of two classes there are experiment class and control class with the sampling technique that are use is cluster random sampling. Methods of data collection used documentation, questionnaires and tests. Techniques of analyzed used analysis of variance two paths with different cell with a significance level of 5%. Results of the data analysis was obtained: (1) there is a different effect between Problem Based Learning and Group Investigation toward mathematics learning outcomes, (2) there is a different effect of student motivation toward mathematics learning outcomes, and(3) there is no interaction between Problem Based Learning, Group Investigation and student motivation towards mathematics learning outcomes. Keyword: group investigation, mathematics learning outcomes, problem based learning, students motivation.